2006
DOI: 10.1159/000091931
|View full text |Cite
|
Sign up to set email alerts
|

Cytological characterization of sex chromosomes and ribosomal DNA location in <i>Anastrepha</i> species (Diptera, Tephritidae)

Abstract: This paper reports a comparative analysis of heterochromatin organization in the sex chromosomes of the fruit fly Anastrepha. Mitotic chromosomes of eight Anastrepha species from different taxonomic groups were stained with DAPI and chromomycin A3 fluorochromes followed by C-banding. A specific sex-chromosome banding pattern was obtained for each of the analyzed species. Fluorescence in situ hybridization (FISH) was performed to investigate the chromosomal location of rDNA loci. In all cases the rDNA sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 47 publications
8
66
1
4
Order By: Relevance
“…Solferini and Morgante (1987) described the mitotic chromosomes of this species using C-banding techniques, and recently Goday et al (2006), using sequential fluorochrome staining, showed that blocks of heterochromatin have differential affinities for the fluorochromes DAPI and CMA 3 ( Figure 1C). For the comparisons that will be made in the present analysis, the description of the A. serpentina chromosomes will be briefly summarized below and shown in the idiogram in Figure 3.…”
Section: Anastrepha Serpentinamentioning
confidence: 95%
See 4 more Smart Citations
“…Solferini and Morgante (1987) described the mitotic chromosomes of this species using C-banding techniques, and recently Goday et al (2006), using sequential fluorochrome staining, showed that blocks of heterochromatin have differential affinities for the fluorochromes DAPI and CMA 3 ( Figure 1C). For the comparisons that will be made in the present analysis, the description of the A. serpentina chromosomes will be briefly summarized below and shown in the idiogram in Figure 3.…”
Section: Anastrepha Serpentinamentioning
confidence: 95%
“…At least 25 larvae of the first generation of each species were used for chromosome preparations. Since the chromosomes of A. serpentina were described before by Goday et al (2006), only a few chromosome preparations were made for the present analysis in order to compare them with the karyotypes of the other two species.…”
Section: Chromosome Preparation Staining and In Situ Hybridizationmentioning
confidence: 99%
See 3 more Smart Citations